If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 4 = 37 Reorder the terms: 4 + 3n = 37 Solving 4 + 3n = 37 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3n = 37 + -4 Combine like terms: 4 + -4 = 0 0 + 3n = 37 + -4 3n = 37 + -4 Combine like terms: 37 + -4 = 33 3n = 33 Divide each side by '3'. n = 11 Simplifying n = 11
| x(1x)= | | -1x/9-2=-3 | | 9w=9w+3 | | 5+4r-3=7r+3-2r | | y=1/2(-2)+2 | | 16=-25+n | | 12+n=6 | | 1/4(5x-5)=4 | | x-51=4 | | 22p=198 | | 1.5q-2.8-2.6q=-2.1q-4.7 | | (x+2)(x)(4)=320 | | 7x+12(7)=11 | | 2(a-2)=((a-1)(a-4)) | | 1/2-2/35/6 | | 7x+84=11 | | 6[5-(-3x-9)]=72x+246 | | 12(3x-9)=3(12x+1) | | 3t^2+t=0 | | 2z+3z-z=16 | | 8z-2z+z=14 | | 14z-12z-2z+z=5 | | 3q-2q=12 | | 10a^2+600a=0 | | 10a^2+600a^2=0 | | 8p-6p=14 | | g/6+44=49 | | 40-9x=88-20-9x | | 7x^4+23x^3y+6x^2y^2=0 | | x+(x+.12)=765 | | 5=k/4-3 | | 6ay^3+7ay^2-5ay=0 |